ANALISIS DATA SEKUNDER: KORELASI ANTARA KADAR FERRITIN DENGAN AST DAN ALT PADA PASIEN THALASEMIA β MAYOR DI RSUPN DR. CIPTO MANGUNKUSUMO JAKARTA TAHUN 2024 - Setiawan, Heru; Mawati, Nenni (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Thalassemia is a chronic hemolytic disease caused by a genetic disorder inherited in an autosomal recessive manner. Thalassemia is characterized by a decrease or reduction in the production of globin chains, causing erythrocytes to become fragile, and results in various degress. Thalassemia sufferers need regular blood transfusions throughout their lives, which results in a buildup or excess of iron, causing disruption in the function of the body’s organs, ane of which is the liver. Ferritin is needed to see excess or storage of iron in the body, while AST and ALT are needed to describe damage the liver function due to iron accumulation. This study aims to determine the correlation between ferritin levels with AST and ALT in thalassemia β major patient in RSUPN Dr. Cipto Mangunkusumo for the period January-March 2024. The method of research is a correlative analytical study with total MR data is 102 thalassemia β major patients who met the inclusion and exclusion criteria using the Spearman correlation test. The result of this research, the average ferritin level was 8080.44 μg/L, the average AST level was 49.23 U/L and the avarage ALT level was 44.05 U/L. The results of the Spearman correlation test showed a correlation between ferritin levels and AST (p=0.000) with a positive direction (r=0.414) and ferritin between ALT (p=0.000) with a positive direction (r=0.415) with significance (α= 5%) in thalassemia β major patient in RSUPN Dr. Cipto Mangunkusumo. From this research, it is clear that thalasemia β major patients should continue to run for reduce the level of morbidity and mortality.